2017
DOI: 10.1080/0035919x.2017.1285367
|View full text |Cite
|
Sign up to set email alerts
|

Graphite oxidation and SEM as a tool for microstructural investigation

Abstract: The microstructure of graphite and its oxidation have been individually investigated at length. When any catalytic impurities are removed from graphite, oxidative attack takes place preferentially from the exposed edges, or active sites of graphite crystallites. This provides valuable insights regarding the underlying crystallography and fundamental structure of graphite which are not immediately evident from a raw topographical examination using, for example, microscopy. Using new techniques, such as field em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…This confirmed that graphene oxide had been reduced. Similar result was obtained by Badenhorst (2017) [43]. Moreover, in all the RGO samples, corrugated surface was observed.…”
Section: Scanning Electron Microscopy Analysis Of Rgossupporting
confidence: 90%
See 2 more Smart Citations
“…This confirmed that graphene oxide had been reduced. Similar result was obtained by Badenhorst (2017) [43]. Moreover, in all the RGO samples, corrugated surface was observed.…”
Section: Scanning Electron Microscopy Analysis Of Rgossupporting
confidence: 90%
“…Each sheet can also be identified from their edges. A similar observation was also reported by Badenhorst (2017), [43]. For GO12H in Figure 4b, there is an ultra-thin layer with folded edges, showing a surface which appeared to be continuous.…”
Section: Scanning Electron Microscopy Analysis Of Graphite and Gos Po...supporting
confidence: 89%
See 1 more Smart Citation
“…Table 2 summarizes the most relevant publication on SEM for nuclear graphite characterization. Badenhorst 2017 [23] This publication provides a comparison between SEM micrographs of oxidized surfaces of a natural graphite and NBG-18.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%